PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN SOSIOLOGI - Nur, Dahniar; Rezki HS, Nur Fitriani; Nurindah; Nursia (Jurnal Pendidikan dan Pembelajaran, 2023)
This research was conducted to explore how the Problem-Based Learning Model can increase student participation and learning achievement. This research discusses the application of the Problem-Based Learning Model in increasing student participation and learning achievement at SMA Negeri 10 Maros in the subject of Sociology. This approach is implemented through two cycles using the Classroom Action Research method. The first cycle showed that problem-based learning required adjustments for students who were not used to it, with a learning completeness of 45.2%. The second cycle showed significant improvement, achieving a learning completeness of 77.4%. These results reflect positive changes in students' attitudes, interests, and activity, as well as an increase in their ability to complete individual and group assignments. The Problem-Based Learning Model has proven to be effective in improving the learning outcomes of sociology students, along with changes in attitudes and more active involvement in the learning process.